2012
DOI: 10.1002/hep.25713
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of oval-cell–mediated liver regeneration in rats

Abstract: We have analyzed the architectural aspects of progenitor-cell-driven regenerative growth in rat liver by applying the 2-acetaminofluorene/partial hepatectomy experimental model. The regeneration is initiated by the proliferation of so-called oval cells. The oval cells at the proximal tips of the ductules have a more differentiated phenotype and higher proliferative rate. This preferential growth results in the formation of a seemingly random collection of small hepatocytes, called foci. These foci have no clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…In a separate study, the size of liver lobules was determined before (n ¼ 4) and 7 d after portal vein ligation (n ¼ 4) as previously described [17,18]. Briefly, hepatic veins and sinusoids were filled up through the inferior vena cava by a fluorescent dye containing polystyrene resin.…”
Section: Liver Lobule Size Determinationmentioning
confidence: 99%
“…In a separate study, the size of liver lobules was determined before (n ¼ 4) and 7 d after portal vein ligation (n ¼ 4) as previously described [17,18]. Briefly, hepatic veins and sinusoids were filled up through the inferior vena cava by a fluorescent dye containing polystyrene resin.…”
Section: Liver Lobule Size Determinationmentioning
confidence: 99%
“…Thus, we aimed to characterize the expression pattern of TJ components, mainly claudins, in endodermlike and hepatocyte-like cells differentiated from HUES cell lines. The differentiated cells were characterized by morphological analysis [46], functional assays, and expression profiles of cytokeratins and ABC transporters characteristic of liver cells.…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds PH may be particularly relevant to clinical scenarios in which the quantity of liver tissue is a limiting factor, such as small-for-size syndrome following liver transplantation and necrosis, inflammation, fibrosis accompanying regeneration in acute viral hepatitis, and other liver diseases (Rutherford & Chung 2008;Curado & Stainier 2010). Following two-thirds PH, cells other than hepatocytes also contribute to the liver regeneration (Dezso et al 2012). Our results showed that biliary epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Following two‐thirds PH, cells other than hepatocytes also contribute to the liver regeneration (Dezso et al . ). Our results showed that biliary epithelial cells (Fig.…”
Section: Discussionmentioning
confidence: 97%